The missio Dei as context for a ministry to refugees - Diniz R. Soares; George Lotter; Sarel J. van der Merwe (In die Skriflig, 2017)
The current global escalation of refugees and involuntary migration, due to the effects of war and world disasters, makes it imperative to devise an effective approach to care for refugees. This article, therefore examines the problem of displacement from the perspective of missio Dei. It presents God’s active involvement in his creation, recreating it and providing particular care for the vulnerable and refugees.